ARID1A mutations in lung cancer: biology, prognostic role, and therapeutic implications - Jin, Fukang; Yang, Zhiguang; Shao, Jingbo; Tao, Jianxin; Reißfelder, Christoph; Loges, Sonja; Zhu, Lei; Schölch, Sebastian (Trends in molecular medicine, 2023)
Mutations in the AT-interacting domain-rich protein 1A (ARID1A) gene, a critical component of the switch/sucrose nonfermentable (SWI/SNF) complex, are frequently found in most human cancers. Approximately 5-10% of lung cancers carry ARID1A mutations. ARID1A loss in lung cancer correlates with clinicopathological features and poor prognosis. Co-mutation of ARID1A and epidermal growth factor receptor (EGFR) results in the limited efficacy of EGFR tyrosine kinase inhibitors (EGFR-TKIs) but increases the clinical benefit of immune checkpoint inhibitors (ICIs). ARID1A gene mutation plays a role in cell cycle regulation, metabolic reprogramming, and epithelial-mesenchymal transition. We present the first comprehensive review of the relationship between ARID1A gene mutations and lung cancer and discuss the potential of ARID1A as a new molecular target.
Online verfügbar 11 May 202323
Gesehen am 05.10.2023